Tirofiban for the treatment of ischaemic stroke - Bukow, Simone; Daffertshofer, Michael; Hennerici, Michael G. (Expert opinion on pharmacotherapy, 2006)
Tirofiban is one of three glycoprotein IIb/IIIa receptor antagonists approved by the US FDA, beside abciximab and eptifibatide. The approval of tirofiban covers conservative treatment of myocardial infarction and unstable angina, as well as percutaneous coronary intervention, for which treatment with tirofiban is recommended in moderate-to-high-risk patients. The efficacy of glycoprotein IIb/IIIa antagonists in myocardial infarction indicated that these agents may also be helpful in the treatment of acute ischaemic stroke. Although experimental data are lacking, observational studies are promising. In recent years, increasing effort in studying glycoprotein IIb/IIIa antagonists has been made, mostly for treatment with abciximab. However, there is one Phase II trial that investigated treatment with tirofiban.